A Monte Carlo Simulation study on the Gamma Radiation Shielding Properties of Concrete with PET Plastic Composite using the PHITS Code - Aye, Myat Mon; Ko, Thaw Tun (The Indonesian Journal of Computer Science, 2024)
The gamma radiation shielding properties of four different types of PET concretes, containing 0 %, 5 %, 10 %, and 15 % PET additives, were simulated using the PHITS code. The simulation covered photon energy levels ranging from 0.01 to 1.5 MeV and employed a NaI (Tl) scintillation detector. Parameters such as the linear attenuation coefficient (LAC), mass attenuation coefficient (MAC), half-value layer (HVL), and mean free path (MFP) were calculated to evaluate the gamma-ray attenuation for each photon energy level. The effectiveness of PET plastics as a radiation shield depends on factors like material thickness, the type of radiation, and specific application requirements. However, this research provides valuable insights into repurposing waste PET plastics to enhance the radiation-shielding properties of concrete, contributing to improved waste management practices and the development of radiation-shielding materials. The results obtained from the PHITS code align satisfactorily with both the simulation results and the theoretical XCOM data.